2021
DOI: 10.1111/jfs.12930
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots‐based fluorescence immunoassay for detection of tiamulin in pork

Abstract: Tiamulin (TML) is a kind of diterpenoid veterinary antibiotic. If abused, it will cause residues in edible tissues of animals and endanger human health. Thus, a facile, sensitive, and accurate method is essential for TML detection. In this study, TML complete antigen was synthesized by oximation and active ester method, and monoclonal antibodies with high specificity and sensitivity were prepared. ZnCdSe/ZnS quantum dots (QDs) coupled with goat anti‐mouse IgG were used as a fluorescence detection probe to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Generally, the luminescence peak position of CdSe/ZnS core/shell QD is usually determined by the band gap of CdSe, and it is not affected by its hydrodynamic size or ligands [ 34 ]. Moreover, the fluorescence intensity of the QD@Ab complex is slightly lower than that of free QD, which may be caused by the dilution of QD in the reaction process, or due to loss in the centrifugation step [ 35 ]. Still, no shift was found in the maximum emission peak compared with that of the free QD, which suggests that the coupling of antibodies did not change the luminescence properties of the QD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the luminescence peak position of CdSe/ZnS core/shell QD is usually determined by the band gap of CdSe, and it is not affected by its hydrodynamic size or ligands [ 34 ]. Moreover, the fluorescence intensity of the QD@Ab complex is slightly lower than that of free QD, which may be caused by the dilution of QD in the reaction process, or due to loss in the centrifugation step [ 35 ]. Still, no shift was found in the maximum emission peak compared with that of the free QD, which suggests that the coupling of antibodies did not change the luminescence properties of the QD.…”
Section: Resultsmentioning
confidence: 99%
“…Still, no shift was found in the maximum emission peak compared with that of the free QD, which suggests that the coupling of antibodies did not change the luminescence properties of the QD. Several studies have also shown that the covalent binding of antibodies to QD using NHS/EDC chemistry does not significantly alter their luminescence properties [ 35 , 36 ]. To gain better insight into the behavior of the QD in presence and absence of the antibodies, we investigated the changes in the QD-excited state lifetime, by acquiring and analyzing the fluorescence lifetime images of free QD ( Figure 4 b) and the QD@Ab ( Figure 4 c) complex grafted onto the paper fibers under a fixed excitation wavelength of 405 nm.…”
Section: Resultsmentioning
confidence: 99%